Bilinear Acute Monocytic Leukemia/B BCR ABL positive. presentation of a case - Tello Vera , Stalin (2023)
Background: Leukemias with an ambiguous phenotype are classified as undifferentiated leukemias and mixed phenotypes, these in turn can be divided into bilinear or biphenotypic and are usually associated with a poor prognosis, especially if they are accompanied by aggressive translocations such as the Philadelphia chromosome. Case report: We present the case of an elderly adult patient who presented acute bilinear leukemia with the presence of a population of monoblastic lineage precursors and another, B lymphoid, evaluated by flow cytometry studies, who also presented the BCR-ABL transcript. , detected by real-time PCR studies. The patient had a poor evolution and died 11 days after her diagnosis. Conclusion: Mixed phenotype leukemias have a poor prognosis and require early diagnosis by flow cytometry and molecular biology to provide timely treatment.